2011
DOI: 10.5152/akd.2011.132
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of chronic biomass fuel smoke exposure on peripheral endothelial functions: an observational study

Abstract: ÖZETAmaç: Hayvansal biyokütle yakıtı (tezek) dumanı inhalasyon ürünlerine kronik olarak maruz kalan bireylerde endoteliyal fonksiyonların değer-lendirilmesi. Yöntemler: Doğumlarından itibaren tezek dumanı inhalasyon ürünleri maruziyeti olan 47 sağlıklı birey (ortalama yaş 31.6±6.8 yıl, 21 erkek) enine kesitli gözlemsel çalışmaya dahil edildi. Kontrol grubu ise 32 sağlıklı kişiden (ortalama yaş 27.9±4.4 yıl, 11 erkek) oluşturuldu. Tüm bireylerde, karotis intima media kalınlığı (CIMT), akım ile ilişkili dilatasy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Two showed significant associations with higher carotid intima media thickness (CIMT),14,30 and one also with the prevalence of carotid plaque ascertained by ultrasound (OR 2.55, 95%CI 1.08-5.98) 30. Against this, a third study found no association with CIMT, although exposure was significantly related to reduced flow-associated dilatation and lower endothelium-independent vasodilatation of the brachial artery 15. In the fourth study, reported only as an abstract, flow-mediated dilatation of the brachial artery again tended to be lower in people using biomass fuels, especially if there was no chimney in the kitchen 32.…”
Section: Resultsmentioning
confidence: 92%
“…Two showed significant associations with higher carotid intima media thickness (CIMT),14,30 and one also with the prevalence of carotid plaque ascertained by ultrasound (OR 2.55, 95%CI 1.08-5.98) 30. Against this, a third study found no association with CIMT, although exposure was significantly related to reduced flow-associated dilatation and lower endothelium-independent vasodilatation of the brachial artery 15. In the fourth study, reported only as an abstract, flow-mediated dilatation of the brachial artery again tended to be lower in people using biomass fuels, especially if there was no chimney in the kitchen 32.…”
Section: Resultsmentioning
confidence: 92%
“…Few studies, however, have examined the relationship between household air pollution from burning biomass fuels and endothelial function markers. One recent study by Buturak et al found that flow mediated dilation and endothelial-independent vasodilation were reduced in individuals with biomass fuel exposure (Butarak et al 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, observational studies have found higher blood pressure (Baumgartner et al 2011; Burroughs Peña et al 2015; McCracken et al 2007); a thicker carotid intima-media complex (Painschab et al 2013), and an increased prevalence of self-reported coronary heart disease, stroke and diabetes in populations chronically exposed to biomass fuel smoke (Lee et al 2012). The mechanisms proposed include lung-mediated inflammation with a systemic release of cytokines (Barregard et al 2006), oxidative stress (Banerjee et al 2012), endothelial dysfunction (Allen et al 2011; Butarak et al 2011) and thrombogenesis (Ray et al 2006), all of which could lead to atherosclerosis and adverse health outcomes (Brevetti et al 2006; Fichtlscherer et al 2004; Verma et al 2002). …”
Section: Introductionmentioning
confidence: 99%
“…11-13 Exposure from solid fuel smoke induces oxidative stress and systemic inflammation, which can lead to high blood pressure and tachycardia. 5 Smoke from solid fuels impairs endothelial and smooth muscle function in blood vessels, increases coagulation tendency and promotes platelet activation , 5,14 thus predisposing to atherosclerosis, which can lead to coronary heart disease and stroke. Furthermore, long-term exposure to smoke from solid fuel has been linked with impaired systolic and diastolic function of the heart.…”
Section: Introductionmentioning
confidence: 99%